2008
DOI: 10.1111/j.1365-2443.2008.01181.x
|View full text |Cite
|
Sign up to set email alerts
|

HMRF1L is a human mitochondrial translation release factor involved in the decoding of the termination codons UAA and UAG

Abstract: While all essential mammalian mitochondrial factors involved in the initiation and elongation phases of translation have been cloned and well characterized, little is known about the factors involved in the termination process. In the present work, we report the functional analysis of human mitochondrial translation release factors (RF). Here, we show that HMRF1, which had been previously denoted as a human mitochondrial RF, was inactive in in vitro translation system, although it is a mitochondrial protein. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 58 publications
7
48
0
Order By: Relevance
“…Even though the bacterial and the mitochondrial ribosomes are bound to be rather different overall, the fact that the decoding region of the mitochondrial 9S and the bacterial 16S RNA are conserved in secondary structure 4,29 strongly suggests that this also pertains on the local three-dimensional structure. This is also supported by the strong sequence conservation between RF1 and mtRF1a in the decoding region, which, together with the fact that the experimentally observed specificity of mtRF1a on bacterial ribosomes 11,12 , is reproduced here, strengthens the reliability of our derived homology models.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Even though the bacterial and the mitochondrial ribosomes are bound to be rather different overall, the fact that the decoding region of the mitochondrial 9S and the bacterial 16S RNA are conserved in secondary structure 4,29 strongly suggests that this also pertains on the local three-dimensional structure. This is also supported by the strong sequence conservation between RF1 and mtRF1a in the decoding region, which, together with the fact that the experimentally observed specificity of mtRF1a on bacterial ribosomes 11,12 , is reproduced here, strengthens the reliability of our derived homology models.…”
Section: Discussionsupporting
confidence: 62%
“…It is also a distinct possibility that mtRF1 is, in fact, the major release factor in vertebrate mitochondria, as mtRF1 has apparently not been tested in knockdown experiments. In this respect, measurements of release activity on bacterial ribosomes 11,12 may be less relevant for the activity on the mitoribosome. It should also be mentioned that earlier homology modelling suggested that mtRF1 cannot read any codon but recognizes ribosomes with an empty A-site 32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,11 Subsequent biochemical and in vivo analyses, however, failed to reveal any release activity associated with this protein. 12,13 After further bioinformatic mining, a second candidate emerged. This protein had greater similarity in sequence and length to each of the two sequence recognition domains present in RF1-rather than RF2-type proteins and was therefore termed mtRF1a.…”
Section: Terminating Human Mitochondrial Protein Synthesismentioning
confidence: 99%